2021
DOI: 10.3390/s21010244
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Neural Network-Based Feature Fusion for Bearing Fault Diagnosis

Abstract: This paper presents a novel method for fusing information from multiple sensor systems for bearing fault diagnosis. In the proposed method, a convolutional neural network is exploited to handle multiple signal sources simultaneously. The most important finding of this paper is that a deep neural network with wide structure can extract automatically and efficiently discriminant features from multiple sensor signals simultaneously. The feature fusion process is integrated into the deep neural network as a layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…where f 1 is the coefficient related to bearing type and bearing load, and p 1 is the load (unit: N) for calculating the bearing friction torque. After determining the bearing friction torque, the calorific value generated by frictional heating is calculated according to (17):…”
Section: Dynamic Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where f 1 is the coefficient related to bearing type and bearing load, and p 1 is the load (unit: N) for calculating the bearing friction torque. After determining the bearing friction torque, the calorific value generated by frictional heating is calculated according to (17):…”
Section: Dynamic Simulation Modelmentioning
confidence: 99%
“…For example, Gao et al used the rolling bearing fault diagnosis method based on the entropy fusion feature of complementary ensemble empirical mode decomposition [16]. Hoang et al observed that the convolutional neural network processed multiple signal sources simultaneously and was constrained by sensor functions [17]. Jiao et al proposed a new bearing fault diagnosis method based on the least squares support vector machine for feature-level fusion and the Dempster-Shafer (DS) evidence theory for decision-level fusion [18].…”
Section: Introductionmentioning
confidence: 99%
“…For 2D-CNN models, vibration data cannot be used in their raw form. Rather, they are initially converted into time-frequency image representations such as spectrograms [38][39][40], scalograms [40,41] or other types of vibration images [42]. Then these images which represent the vibration signal in image form are used as input in 2D-CNN model.…”
Section: Introductionmentioning
confidence: 99%
“…Deep neural networks have extensive applications in artificial intelligence mainly including computer vision [1][2][3][4][5][6][7][8], speech recognition [9][10][11][12][13], medical detection [14][15][16][17][18][19], and mechanical fault diagnosis [20][21][22][23][24][25][26][27][28]. Compared with human ability, the DNN model is more capable of solving this complicated problem.…”
Section: Introductionmentioning
confidence: 99%